2003
DOI: 10.1034/j.1600-0412.2003.00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatment with gonadotropin releasing hormone agonist on the uterine leiomyomata structure

Abstract: Our data strengthen the hypothesis that the uterine leiomyoma response to steroid hormones results from the presence of specific hormone receptors, and progesterone receptors may also play a role in the development of leiomyoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…A few descriptive studies have evaluated the expression of Ki‐67 and endothelial cell marker CD31 in fibroids, with no reference to tumor size. Other morphological features, such as smooth muscle cell density and collagen content, have been examined, mainly in the evaluation of response to GnRHa, with contradictory results. A single study has attempted to predict clinical growth of fibroids by means of histological examination of fibroid biopsies and magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…A few descriptive studies have evaluated the expression of Ki‐67 and endothelial cell marker CD31 in fibroids, with no reference to tumor size. Other morphological features, such as smooth muscle cell density and collagen content, have been examined, mainly in the evaluation of response to GnRHa, with contradictory results. A single study has attempted to predict clinical growth of fibroids by means of histological examination of fibroid biopsies and magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…GnRHa undoubtedly induce fibroid tumor shrinkage, the degree of which has been shown to be directly proportional to the percentage of cells that are estrogen receptor positive, thus implicating estrogen as a major effector of tumor growth and its reduction as the central mechanism of fibroid shrinkage with GnRHa therapy 78. Chegini et al found evidence of suppression of signal transduction pathways involving growth factors, ovarian steroids, and adhesion molecules with a resulting decrease in DNA synthesis, cell proliferation, and production of transforming growth factor-b 79,80.…”
Section: Managementmentioning
confidence: 99%
“…Besides a reduction of size, increased cellularity, necrosis, decreased cell volume, atrophy, diminished microfilaments, mitochondrial swelling, pyknosis, and cellular deformity are also reported [10][11][12][13]. In leiomyomas without lymphoid infiltration, modulation of the reactivity of progesterone and estrogen receptors is detected as well [14]. In our case, the alterations were observed mainly in the reactivity of leiomyocytes for LAMPs.…”
Section: Discussionmentioning
confidence: 48%